DNA Hydrogel with Tunable pH‐Responsive Properties Produced by Rolling Circle Amplification. Issue 72 (30th November 2017) - Xu, Wanlin; Huang, Yishun; Zhao, Haoran; Li, Pan; Liu, Guoyuan; Li, Jing; Zhu, Chengshen; Tian, Leilei
Abstract: Recently, smart DNA hydrogels, which are generally formed by the self‐assembly of oligonucleotides or through the cross‐linking of oligonucleotide–polymer hybrids, have attracted tremendous attention. However, the difficulties of fabricating DNA hydrogels limit their practical applications. We report herein a novel method for producing pH‐responsive hydrogels by rolling circle amplification (RCA). In this method, pH‐sensitive cross‐linking sites were introduced into the polymeric DNA chains during DNA synthesis. As the DNA sequence can be precisely defined by its template, the properties of such hydrogels can be finely tuned in a very facile way through template design. We have investigated the process of hydrogel formation and pH‐responsiveness to provide rationales for functional hydrogel design based on the RCA reaction. Abstract : A defining template : A strategy to prepare stimuli‐responsive DNA hydrogels has been developed based upon a one‐step rolling circle amplification (see figure). In this method, pH‐sensitive cross‐linking sites were introduced into the polymeric DNA chains during DNA synthesis. As the DNA sequence can be precisely defined by its template, the properties of such hydrogels can be finely tuned in a very facile way.